Why LGBT Teachers May Make Exceptional School Leaders - Lee, Catherine (Frontiers in Sociology, 2020)
The recent school gate protests about the inclusion of LGBT identities in the curriculum suggest that sexual identity remains an issue of moral panic in UK schools. Given this current climate, and the legacy of Section 28, schools have rarely been easy workplaces for LGBT teachers. For LGBT teachers, significant energy and vigilance is required then to navigate the heteronormative and cis-normative staffroom and classroom. There is evidence that LGBT teachers try to remain as invisible as possible in their schools so as to not draw attention to themselves (Lee, 2019a). Some avoid promotion to school leadership roles fearing that the status will necessitate greater personal scrutiny by school stakeholders. Based on key attributes including, reading people, compassion and commitment to the inclusion of others, making connections managing uncertainty, courage and risk-taking, this perspective piece argues that some of the strategies LGBT teachers deploy to manage the intersection of personal and professional identities in school equip them with an array of particular skills that are conducive to excellent school leadership.